Neurodegenerative Diseases Clinical Aspects, Molecular Genetics and Biomarkers - Galimberti, Daniela; Scarpini, Elio (Springer London : Imprint: Springer, 2014)
This book gives an overview of the current knowledge on the most common neurodegenerative diseases, including Alzheimer's disease, frontotemporal lobar degeneration, amyotrophic lateral sclerosis, and additional neurodegenerative diseases. Different aspects of each disease are reviewed, including clinical issues, treatments, basic discoveries (genetics and molecular biology), and translation of basic research into biomarkers for early diagnosis. In addition, emerging data indicate that neurodegeneration seems to also be present in classically non-degenerative disorders. Therefore, a chapter about overlapping mechanisms between dementias and psychiatric disorders is included, as well as a description of the role of neurodegeneration in multiple sclerosis.   Neurodegenerative Diseases is aimed at clinicians, particularly those working in academic hospitals. This multidisciplinary book will also be of interest to basic researchers in medical fields.